The Effect of Human Growth Index and Investment on Economic Growth in Central Java Province - Bado Riyono; Sumaryoto; Meirinaldi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Investment and the human development index (IPM) have an important role in maintaining economic growth in the province of Central Java. This study aims to determine the effect of investment on economic growth, the effect of HDI on economic growth, and the effect of investment and HDI on economic growth. The research method used is a quantitative one. The data were taken from the Central Java Bureau of Statistics from 2017 to 2021. The classic test was carried out using the normality, heteroscedasticity, and multiplierity tests. After that, several hypothesis tests were carried out, such as the Coefficient of Determination Test (R2), the F test, and the t test. The results showed that, there is an effect of investment on economic growth; there is an effect of HDI on economic growth; and there is an effect of investment and HDI on economic growth. These results can be the basis for further research.